Effect of commercial inoculants on fermentation of 1988 silage crops - K.K. Bolsen; A. Laytimi; S. Azimi; R.A. Hart; F. Niroomand; J. Bradford; L. Clare (Kansas Agricultural Experiment Station Research Reports, 1989)
We have measured silage fermentation dynamics in over 50 crops since the development of a 4 x 14 inch PVC pipe, laboratory-scale silo in 1984. In many of these experiments, our objective was to determine how inoculants or inoculant/enzyme combinations affected the rate and efficiency of the ensiling process. Twenty-five different inoculants have been tested over a wide range of ensiling conditions. Results show that the majority of silage inoculants available today are able to supply a high number of lactic acid bacteria (LAB) and to improve silage fermentation in most crops (KAES, Reports of Progress 494, 514, and 539). Preliminary results of 17 experiments conducted in 1988 to determine the efficacy of 12 commercial inoculants are summarized here. An additional objective in six experiments was to study the effect of numbers of LAB supplied to the crop by inoculants on fermentation response. In two alfalfa experiments, combinations of inoculant and dextrose (fermentable sugar) and inoculant and enzyme (to increase fermentable sugar) were compared.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Innoculants; Silage